Synthesis method of indium-tin alloy material used in photoelectric field

The preparation of indium tin alloys doped with zirconium metal through high-energy ball milling and pulse current sintering technology has solved the problem of insufficient mechanical and electrical properties of traditional indium tin alloys, achieved high density, high conductivity and high hardness, and improved its application potential in the field of optoelectronics.

CN119592830APending Publication Date: 2025-03-11LIUZHOU HUAXI COLORED DESIGN & RESEARCH INSTITUTE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411792428.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-07
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The preparation method of traditional indium tin alloys has problems such as uneven distribution of doping elements, insufficient microstructure control and many structural defects, resulting in insufficient mechanical and electrical properties in the field of photoelectricity.

Method used

High-energy ball milling technology and pulse current sintering technology are used to prepare indium tin alloys doped with zirconium metal. By optimizing parameters such as ball milling time, ball milling speed, sintering temperature and current density, the microstructure and performance of the alloy are improved.

Benefits of technology

It significantly improves the microstructure and performance of indium tin alloy, achieves the goals of high density, high conductivity and high hardness, and enhances its application potential in the field of optoelectronics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to the technical field of non-ferrous metal application, in particular to a synthetic method of an indium-tin alloy material for the photoelectric field, which comprises the following steps: preparing raw materials: primarily mixing indium metal powder, tin metal powder and zirconium metal powder; dispersing the raw material powder, namely transferring the primarily mixed raw materials into a high-energy ball mill for dispersing; performing powder pretreatment, namely performing vacuum drying on the dispersed raw material powder; carrying out pulse current sintering, namely transferring the dried raw material powder into pulse current sintering equipment for sintering; and post-treatment is conducted, specifically, an alloy block obtained after powder sintering is conducted on the raw material powder is cut, and the indium-tin alloy material is obtained. According to the indium-tin alloy material, the high-energy ball milling and pulse current sintering technologies are combined, the doping concentration and the alloy microstructure can be controlled, and the indium-tin alloy material which is suitable for the photoelectric field and has good alloy uniformity, defect density, mechanical property and electrical property is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nonferrous metal application, and in particular to a method for synthesizing an indium-tin alloy material used in the optoelectronics field. Background Art

[0002] Indium tin alloy (In-Sn alloy) is widely used in optoelectronics, electronic packaging, low-temperature welding and other fields due to its low melting point, excellent conductivity and ductility.

[0003] However, the traditional preparation method of indium tin alloy has some inherent deficiencies in the preparation process, such as uneven distribution of doping elements, insufficient control of alloy microstructure and high structural defects. These problems directly lead to the mechanical and electrical properties of indium tin alloy in the optoelectronic field, severely limiting the potential of indium tin alloy in the application of optoelectronics.

[0004] Therefore, there is a need for an indium tin alloy material that can achieve better mechanical and electrical properties. Summary of the invention

[0005] The main purpose of the present invention is to provide a method for synthesizing an indium tin alloy material for use in the optoelectronic field, aiming to solve the problem that the mechanical properties and electrical properties of the existing indium tin alloy are insufficient.

[0006] To achieve the above object, the present invention provides a method for synthesizing an indium tin alloy material for use in the optoelectronic field, the method comprising the following steps:

[0007] Raw material preparation: preliminarily mixing indium metal powder, tin metal powder and zirconium metal powder;

[0008] Disperse raw material powders and transfer the raw materials after initial mixing into a high-energy ball mill for dispersion;

[0009] Powder pretreatment, vacuum drying of the dispersed raw material powder;

[0010] Pulse current sintering: the dried raw material powder is moved into the pulse current sintering equipment for sintering;

[0011] After the treatment, the alloy block obtained after sintering the raw material powder is cut into pieces to obtain the indium tin alloy material.

[0012] Furthermore, the raw materials include 47% to 52wt% indium metal powder, 47 to 52wt% tin metal powder and 1 to 3wt% zirconium metal powder by weight.

[0013] Furthermore, the step of dispersing the raw material powder and moving the raw materials after the initial mixing into a high-energy ball mill for dispersion includes:

[0014] Place the raw material powder after initial mixing in a high-energy ball mill, set the ball milling speed to 350-450prm, the ball milling time to 20-24 hours, and the ball-to-material ratio to 9:1-10:1;

[0015] Start the high energy ball mill and add an alcohol based dispersant to the raw material powder;

[0016] Regularly check the powder state during the ball milling process, and stop the machine every 4 to 5 hours to check the uniformity and particle fineness of the powder until the high-energy ball mill completes the dispersion of the raw material powder.

[0017] Furthermore, the alcohol-based dispersant can be ethanol, and the added amount of ethanol is 1.5-2.5% of the total mass of the powder.

[0018] Furthermore, the powder pretreatment step of vacuum drying the dispersed raw material powder includes:

[0019] The dispersed raw material powder is removed from the high energy ball mill and transferred to a vacuum drying oven;

[0020] The temperature of the vacuum drying oven is set to 80-90° C., and the drying time is set to 12-24 hours to vacuum dry the dispersed raw material powder.

[0021] Furthermore, the pulse current sintering step of moving the dried raw material powder into the pulse current sintering equipment for sintering comprises:

[0022] Move the dried raw material powder into the mold and ensure that the raw material powder in the mold is evenly distributed;

[0023] Place the mold in the pulse current sintering equipment, set the sintering temperature to 300-600℃, and the pulse current density to 1000-1200A / cm 2 , the holding time is 8 to 10 minutes, and the applied pressure is 50 to 60 MPa;

[0024] The pulse current sintering equipment is started, and the temperature and current density of the pulse current sintering equipment are regularly detected until the sintering is completed to obtain an alloy block.

[0025] Furthermore, the post-processing step of cutting and polishing the alloy block obtained after sintering the raw material powder to obtain the indium tin alloy material also includes:

[0026] The indium tin alloy block obtained after sintering is taken out from the mold and cooled for 12 to 24 hours until the indium tin alloy block cools to room temperature;

[0027] The indium tin alloy block cooled to room temperature is machined and cut into alloy samples;

[0028] The alloy sample is subjected to surface treatment and performance testing to obtain an indium tin alloy material.

[0029] Furthermore, the steps of performing surface treatment on the alloy sample and performing performance testing on the alloy sample also include:

[0030] Conduct electrical property tests on the alloy samples to determine the resistivity of the alloy samples;

[0031] Conduct mechanical property tests on alloy samples to determine the hardness and strength of the alloy samples;

[0032] The alloy samples are subjected to microstructural testing to determine the microscopic crystal structure of the alloy samples.

[0033] In the present invention, the indium tin alloy metal doped with zirconium metal is prepared by high-energy ball milling technology and pulse current sintering technology, which can significantly improve the microstructure and performance of the indium tin alloy. By setting and optimizing parameters such as ball milling time, ball milling speed, sintering temperature, current density, etc., the goals of high density, high conductivity and high hardness of the indium tin alloy material are achieved. DETAILED DESCRIPTION

[0034] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] It should be noted that all directional indications in the embodiments of the present invention (such as up, down, left, right, front, back, etc.) are only used to explain the relative position relationship, movement status, etc. between the components in a certain specific posture. If the specific posture changes, the directional indication will also change accordingly.

[0036] In addition, the descriptions of "first", "second", etc. in the present invention are only used for descriptive purposes and cannot be understood as indicating or implying their relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In addition, the technical solutions between the various embodiments can be combined with each other, but they must be based on the ability of ordinary technicians in the field to implement them. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such a combination of technical solutions does not exist and is not within the scope of protection required by the present invention.

[0037] The indium-tin alloy involved in the present invention specifically refers to an alloy whose main body is composed of two metals, indium (In) and tin (Sn). The common composition ratio includes In-48Sn (i.e., 48% tin, 52% indium). The obtained indium-tin alloy has good electrical conductivity, ductility, flexibility and a low melting point. Due to its low melting point, indium-tin alloy is often used as a welding material, especially in electronic components that require low-temperature welding. Indium tin oxide (commonly known as ITO) is a compound composed of three elements: indium, tin and oxygen. Because ITO has high transparency, visible light transmittance is usually above 80%, and has high hardness and wear resistance, indium-tin alloy is often prepared as indium tin oxide and then used as a transparent conductive film for solar cells. Therefore, in the preparation process of indium-tin alloy, it is necessary to consider the conductivity and mechanical properties thereof.

[0038] The alcohol-based dispersant in the present invention can be ethanol, and the amount of ethanol added is 1.5-2.5% of the total mass of the powder.

[0039] It can be understood that the alcohol-based dispersant can also be one of isopropanol, ethylene glycol, n-butanol, and glycerol. In detail, when isopropanol is selected as the alcohol-based dispersant, the amount of isopropanol added is 1-3% of the total mass of the powder; when ethylene glycol is selected as the alcohol-based dispersant, the amount of ethylene glycol added is 0.5-2% of the total mass of the powder; when n-butanol is selected as the alcohol-based dispersant, the amount of n-butanol added is 1-3% of the total mass of the powder; when glycerol is selected as the alcohol-based dispersant, the recommended amount of glycerol is 05-2%. The selection and usage of the dispersant play an important role in preventing powder agglomeration and improving mixing uniformity during high-energy ball milling, and the selected When the dosage of the dispersant used is less than the threshold value disclosed in the present invention, it will be difficult to achieve the dispersion effect. When the dosage of the dispersant selected is greater than the threshold value disclosed in the present invention, it will lead to an increase in the liquid bridges between the powder particles, which will cause the powder particles to agglomerate and may also cause the powder to be unevenly dispersed during the high-energy ball milling process. At the same time, too much dispersant may also cause the powder to be unevenly dispersed during the ball milling process, affecting the uniform mixing between different components and causing risks such as drying difficulties and a large amount of residue that affect the performance of the powder. Therefore, the selection of the type and dosage of the dispersant requires a lot of intellectual effort, which is difficult to obtain through simple routine experiments by technicians in this field.

[0040] In detail, powder pretreatment is used to remove dispersants to ensure the smooth progress of the subsequent pulse current sintering process. It can also prevent the residual dispersants from volatilizing during the sintering process, resulting in the formation of pores or other defects, affecting the density and performance of the alloy.

[0041] The following is a comparison of alloy material performance test experiments conducted using Examples 1-3 and Control Examples 1-2. The specific experimental steps are as follows:

[0042] Alloy material preparation:

[0043] Embodiment 1:

[0044] S1. Mix metal powders of zirconium, indium and tin in a ratio of 3wt% zirconium, 47wt% indium and 50wt% tin, put the mixed powder into a ball mill, add ball material (ball milling medium), set the ball milling speed to 350rpm and the ball milling time to 20h;

[0045] S2, start the high-energy ball mill, add ethanol as a dispersant at a mass of 3% of the total powder mass during the ball milling process, and stop the machine every 4 hours to check the uniformity and fineness of the powder;

[0046] S3, taking the powder out of the high-energy ball mill and transferring it to a vacuum drying oven, setting the temperature of the vacuum drying oven to 80° C., setting the drying time to 12 h, and vacuum drying the powder;

[0047] S4. Place the dried powder into a graphite mold and transfer it to a pulse current sintering device. Set the parameters of the pulse current device to 1000A / cm 2 , pulse frequency is 500Hz, sintering temperature is 300℃, sintering time is 1h, and holding time is 8min;

[0048] S5. After sintering is completed, the alloy material is allowed to gradually cool down to room temperature, and finally the alloy material is taken out of the pulse current sintering equipment.

[0049] Embodiment 2:

[0050] S1. Mix metal powders of zirconium, indium and tin in a ratio of 5wt% zirconium, 45wt% indium and 50wt% tin, put the mixed powder into a ball mill, add ball material (ball milling medium), set the ball milling speed to 350rpm and the ball milling time to 22h;

[0051] S2, start the high-energy ball mill, add ethanol as a dispersant at a mass of 3% of the total powder mass during the ball milling process, and stop the machine every 4 hours to check the uniformity and fineness of the powder;

[0052] S3, taking the powder out of the high-energy ball mill and transferring it to a vacuum drying oven, setting the temperature of the vacuum drying oven to 85° C., setting the drying time to 17 h, and vacuum drying the powder;

[0053] S4. Place the dried powder into a graphite mold and transfer it to a pulse current sintering device. Set the parameters of the pulse current device to 1100A / cm 2, pulse frequency is 1000Hz, sintering temperature is 450℃, sintering time is 2h, and holding time is 9min;

[0054] S5. After sintering is completed, the alloy material is allowed to gradually cool down to room temperature, and finally the alloy material is taken out of the pulse current sintering equipment.

[0055] Embodiment 3:

[0056] S1. Mix metal powders of zirconium, indium and tin in a ratio of 7wt% zirconium, 43wt% indium and 50wt% tin, put the mixed powder into a ball mill, add ball material (ball milling medium), set the ball mill speed to 450rpm and the ball milling time to 24h;

[0057] S2, start the high-energy ball mill, add ethanol as a dispersant at a mass of 3% of the total powder mass during the ball milling process, and stop the machine every 4 hours to check the uniformity and fineness of the powder;

[0058] S3, taking the powder out of the high-energy ball mill and transferring it to a vacuum drying oven, setting the temperature of the vacuum drying oven to 90° C., setting the drying time to 20 h, and vacuum drying the powder;

[0059] S4. Place the dried powder into a graphite mold and transfer it to a pulse current sintering device. Set the parameters of the pulse current device to 1200A / cm 2 , pulse frequency is 2000Hz, sintering temperature is 600℃, sintering time is 3h, and holding time is 10min;

[0060] S5. After sintering is completed, the alloy material is allowed to gradually cool down to room temperature, and finally the alloy material is taken out of the pulse current sintering equipment.

[0061] Comparative Example 1:

[0062] S1. Mix indium and tin metal powders in a ratio of 50 wt% indium and 50 wt% tin, put the mixed powder into a ball mill, add ball material (ball milling medium), set the ball mill speed to 450 rpm and the ball milling time to 24 h;

[0063] S2, start the high-energy ball mill, add ethanol as a dispersant at a mass of 3% of the total powder mass during the ball milling process, and stop the machine every 4 hours to check the uniformity and fineness of the powder;

[0064] S3, taking the powder out of the high-energy ball mill and transferring it to a vacuum drying oven, setting the temperature of the vacuum drying oven to 90° C., setting the drying time to 20 h, and vacuum drying the powder;

[0065] S4. Place the dried powder into a graphite mold and transfer it to a pulse current sintering device. Set the parameters of the pulse current device to 1200A / cm 2 , pulse frequency is 2000Hz, sintering temperature is 600℃, sintering time is 3h, and holding time is 10min;

[0066] S5. After sintering is completed, the alloy material is allowed to gradually cool down to room temperature, and finally the alloy material is taken out of the pulse current sintering equipment.

[0067] Comparative Example 2:

[0068] S1. Mix metal powders of zirconium, indium and tin in a ratio of 3wt% chromium, 47wt% indium and 50wt% tin, put the mixed powder into a ball mill, add ball material (ball milling medium), set the ball milling speed to 450rpm and the ball milling time to 24h;

[0069] S2, start the high-energy ball mill, add ethanol as a dispersant at a mass of 3% of the total powder mass during the ball milling process, and stop the machine every 4 hours to check the uniformity and fineness of the powder;

[0070] S3, taking the powder out of the high-energy ball mill and transferring it to a vacuum drying oven, setting the temperature of the vacuum drying oven to 90° C., setting the drying time to 20 h, and vacuum drying the powder;

[0071] S4. Place the dried powder into a graphite mold and transfer it to a pulse current sintering device. Set the parameters of the pulse current device to 1200A / cm 2 , pulse frequency is 2000Hz, sintering temperature is 600℃, sintering time is 3h, and holding time is 10min;

[0072] S5. After sintering is completed, the alloy material is allowed to gradually cool down to room temperature, and finally the alloy material is taken out of the pulse current sintering equipment.

[0073] Alloy material performance test:

[0074] The alloy materials of Examples 1-3 were selected as samples to test the performance of the alloy materials. The specific experimental steps are as follows:

[0075] (I) Density detection

[0076] Method: Helium Pycnometry

[0077] step:

[0078] S1. Dry the alloy material sample to ensure that the sample is free of moisture;

[0079] S2. Place the sample in an airtight measuring chamber;

[0080] S3, filling the measuring chamber with helium to reach equilibrium pressure;

[0081] S4, measuring the volume change of helium and calculating the real volume of the alloy material sample;

[0082] S5. The density of the alloy material sample is obtained by calculating the mass of the sample and the obtained true volume.

[0083] (II) Conductivity detection

[0084] Method: Four-probe method

[0085] step:

[0086] S1. Cut the alloy material sample to ensure that the surface of the alloy material sample is flat;

[0087] S2. Arrange four probes evenly on the sample surface to ensure that each probe has good contact with the sample surface;

[0088] S3, applying a current I through two of the probes;

[0089] S4, measure the voltage drop V through the other two probes;

[0090] S5. Through the formula Calculate the conductivity, where t is the sample thickness and d is the probe spacing.

[0091] (III) Hardness test

[0092] Method: Vickers Hardness Test (Helium Pycnometry)

[0093] step:

[0094] S1. Grind the surface of the alloy material sample to make sure there is no oxide layer and impurities;

[0095] S2. Use a Vickers hardness tester to apply a certain load (usually 100g to 1kg) on ​​the sample surface;

[0096] S3. After unloading the load, the length of the sub-constant diagonal line was measured using a microscope;

[0097] S4, through the formula The Vickers hardness is calculated, where F is the applied load, θ is the indenter angle (136° is selected in the present invention), and d is the average length of the indentation diagonal.

[0098] Table 1 Experimental data of alloy material performance test

[0099]

[0100] Experimental conclusion:

[0101] 1. Density: The density of all three examples is close to the theoretical density, indicating that the high-energy ball milling and pulse current sintering technology effectively improve the compactness of the material, and the highest density is reached in Example 3, indicating that higher temperature is conducive to the compactness of the material. In the control example 1, no zirconium metal is added for doping, and in the control example 2, chromium metal is added for doping. In the control example 1, indium tin alloy is directly prepared by pure indium and pure tin, and the detected density is almost the same as the theoretical density; in the control example 2, indium tin alloy is prepared by doping with chromium metal. Although the density of chromium is greater than that of zirconium, it can still provide better densification sintering performance;

[0102] 2. Electrical conductivity: The electrical conductivity increases with the increase of sintering temperature and current density, and Example 3 has the highest electrical conductivity, indicating that a higher sintering temperature is helpful to improve the electrical properties of the material. In Example 1, the indium tin alloy prepared with pure indium and pure tin has a diffraction effect due to the defects in the spatial structure of the grains, thereby increasing the resistance and reducing the conductivity; in Example 2, the technical solution of doping with chromium metal makes the defects inside the indium tin alloy larger, resulting in a decrease in the conductivity in Example 2;

[0103] 3. Hardness: The hardness increases with the increase of sintering temperature and current density, and the hardness of Example 3 is the highest, indicating that a higher sintering temperature is helpful to improve the mechanical properties of the alloy material. The hardness of the pure indium tin alloy in Example 1 is affected by the lack of other metal doping, and the hardness is reduced; the mechanical properties of the technical solution of chromium metal doping in Example 2 are reinforced to a certain extent.

[0104] Experimental conclusion summary: The zirconium-doped indium tin alloy prepared by high-energy ball milling and pulse current sintering technology can significantly improve the microstructure and performance of the material. Pure indium tin alloy without zirconium metal doping or random doping with other metal elements (such as chromium in control example 2) will reduce the comprehensive performance of the indium tin alloy. The specific implementation effect depends on parameters such as ball milling time, ball milling speed, sintering temperature and current density. By optimizing these parameters, the goals of high density, high conductivity and high hardness of the alloy material can be achieved.

[0105] In combination with all the above embodiments, the indium tin alloy material in the present invention can control the doping concentration and alloy microstructure by combining high-energy ball milling and pulse current sintering technology, so as to obtain an indium tin alloy material suitable for the optoelectronic field and having good alloy uniformity, defect density, mechanical properties and electrical properties.

[0106] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent structural changes made by using the contents of the present invention specification under the inventive concept of the present invention, or direct / indirect application in other related technical fields are included in the patent protection scope of the present invention.

Claims

1. A method for synthesizing an indium tin alloy material for use in the optoelectronics field, characterized in that: The following steps are involved: Raw material preparation: preliminarily mixing indium metal powder, tin metal powder and zirconium metal powder; Disperse raw material powders and transfer the raw materials after initial mixing into a high-energy ball mill for dispersion; Powder pretreatment, vacuum drying of the dispersed raw material powder; Pulse current sintering: the dried raw material powder is moved into the pulse current sintering equipment for sintering; After the treatment, the alloy block obtained after sintering the raw material powder is cut into pieces to obtain the indium tin alloy material.

2. The method for synthesizing an indium tin alloy material for the optoelectronic field according to claim 1, characterized in that: The raw materials include 47% to 52% by weight of indium metal powder, 47% to 52% by weight of tin metal powder and 1% to 3% by weight of zirconium metal powder.

3. The method for synthesizing an indium tin alloy material for the optoelectronic field according to claim 1, characterized in that: The step of dispersing the raw material powder and moving the raw materials after initial mixing into a high-energy ball mill for dispersion comprises: Place the raw material powder after initial mixing in a high-energy ball mill, set the ball milling speed to 350-450prm, the ball milling time to 20-24 hours, and the ball-to-material ratio to 9:1-10:1; Starting the high energy ball mill and adding an alcohol-based dispersant to the raw material powder; Regularly check the powder state during the ball milling process, and stop the machine every 4 to 5 hours to check the uniformity and particle fineness of the powder until the high-energy ball mill completes the dispersion of the raw material powder.

4. The method for synthesizing an indium-tin alloy material for the optoelectronic field according to claim 3, characterized in that: The alcohol-based dispersant can be ethanol, and the added amount of ethanol is 1.5-2.5% of the total mass of the powder.

5. The method for synthesizing an indium tin alloy material for the optoelectronic field according to claim 1, characterized in that: The powder pretreatment step of vacuum drying the dispersed raw material powder includes: The dispersed raw material powder is removed from the high energy ball mill and transferred to a vacuum drying oven; The temperature of the vacuum drying oven is set to 80-90° C., and the drying time is set to 12-24 hours to vacuum dry the dispersed raw material powder.

6. The method for synthesizing an indium tin alloy material for the optoelectronic field according to claim 1, characterized in that: The pulse current sintering step of moving the dried raw material powder into the pulse current sintering equipment for sintering comprises: Move the dried raw material powder into the mold and ensure that the raw material powder in the mold is evenly distributed; Place the mold in the pulse current sintering equipment, set the sintering temperature to 300-600℃, and the pulse current density to 1000-1200A / cm 2 , the holding time is 8 to 10 minutes, and the applied pressure is 50 to 60 MPa; The pulse current sintering equipment is started, and the temperature and current density of the pulse current sintering equipment are regularly detected until the sintering is completed to obtain an alloy block.

7. The method for synthesizing an indium tin alloy material for the optoelectronic field according to claim 1, characterized in that: The post-processing step of cutting and polishing the alloy block obtained after sintering the raw material powder to obtain the indium tin alloy material also includes: The indium tin alloy block obtained after sintering is taken out from the mold and cooled for 12 to 24 hours until the indium tin alloy block cools to room temperature; The indium tin alloy block cooled to room temperature is machined and cut into alloy samples; The alloy sample is subjected to surface treatment and performance testing to obtain an indium tin alloy material.

8. The method for synthesizing an indium tin alloy material for the optoelectronic field according to claim 7, characterized in that: The steps of performing surface treatment on the alloy sample and performing performance testing on the alloy sample also include: Conduct electrical property tests on the alloy samples to determine the resistivity of the alloy samples; Conduct mechanical property tests on alloy samples to determine the hardness and strength of the alloy samples; The alloy samples are subjected to microstructural testing to determine the microscopic crystal structure of the alloy samples.